The cost of safe sex: estimating the price premium for unprotected sex during the Avahan HIV prevention programme in India. Issue 10 (11th October 2019) - Quaife, Matthew; Lépine, Aurélia; Deering, Kathleen; Terris-Prestholt, Fern; Beattie, Tara; Isac, Shajy; Paranjape, R S; Vickerman, Peter
Abstract: There is some evidence that female sex workers (FSWs) receive greater earnings for providing unprotected sex. In 2003, the landscape of the fight against HIV/AIDS dramatically changed in India with the introduction of Avahan, the largest HIV prevention programme implemented globally. Using a unique, cross-sectional bio-behavioural dataset from 3591 FSWs located in the four Indian states where Avahan was implemented, we estimate the economic loss faced by FSWs who always use condoms. We estimate the causal effect of condom use on the price charged during the last paid sexual intercourse using the random targeting of Avahan as an instrumental variable. Results indicate that FSWs who always use condoms face an income loss of 65% (INR125, US$2.60) per sex act compared to peers providing unprotected sex, consistent with our expectations. The main finding confirms that clients have a preference for unprotected sex and that policies aiming at changing clients' preferences and at improving the bargaining power of FSWs are required to limit the spread of HIV.